Endophytic Fungus Isolated From Achyrocline satureioides Exhibits Selective Antiglioma Activity—The Role of Sch-642305 - Pedra, Nathalia Stark; Galdino, Kennia de Cássia Araújo; da Silva, Daniel Schuch; Ramos, Priscila Treptow; Bona, Natália Pontes; Soares, Mayara Sandrielly Pereira; Azambuja, Juliana Hoffstater; Canuto, Kirley Marques; Brito, Edy Sousa de; Ribeiro, Paulo Riceli Vasconcelos; Souza, Ana Sheila de Queiroz; Cunico, Wilson; et al. (Frontiers in Oncology, 2018)
Glioblastoma is the most devastating primary brain tumor. Current treatment is palliative, making necessary the development of new therapeutic strategies to offer alternatives to patients. Therefore, endophytes represent an interesting source of natural metabolites with anticancer potential. These microorganisms reside in tissues of living plants and act to improve their growth. Evidence revealed that several medicinal plants are colonized by endophytic fungi producer of antitumor metabolites. Achyrocline satureioides is a Brazilian medicinal plant characterized by its properties against gastrointestinal disturbances, anticancer and antioxidant effects. However, there are no reports describing the endophytic composition of A. satureioides. The present study proposes the isolation of endophytic fungus from A. satureioides, extract preparation, phytochemical characterization and evaluation of its antiglioma potential. Our data showed that crude extracts of endophyte decreased glioma viability with IC50 values of 1.60–1.63 μg/mL to eDCM (dichloromethane extract) and 37.30–55.12 μg/mL to eEtAc (ethyl acetate extract), respectively. Crude extracts induced cell death by apoptosis with modulation of redox status. In order to bioprospect anticancer metabolites, endophytic fungus extracts were subjected to guided fractionation and purification yielded five fractions of each extract. Six of ten fractions showed selective antiproliferative activity against glioma cells, with IC50 values ranged from 0.95 to 131.3 μg/mL. F3DCM (from eDCM) and F3EtAc (from eEtAc) fractions promoted C6 glioma toxicity with IC50 of 1.0 and 27.05 μg/mL, respectively. F3EtAc fraction induced late apoptosis and arrest in G2/M stage, while F3DCM promoted apoptosis with arrest in Sub-G1 phase. Moreover, F3DCM increased antioxidant defense and decreased ROS production. Additionally, F3DCM showed no cytotoxic activity against astrocytes, revealing selective effect. Based on promising potential of F3DCM, we identified the production of Sch-642305, a lactone, which showed antiproliferative properties with IC50 values of 1.1 and 7.6 μg/mL to C6 and U138MG gliomas, respectively. Sch-642305 promoted arrest on cell cycle in G2/M inducing apoptosis. Furthermore, this lactone decreased glioma cell migration and modulated redox status, increasing superoxide dismutase and catalase activities and enhancing sulfhydryl content, consequently suppressing reactive species of oxygen generation. Taken together, these results indicate that metabolites produced by endophytic fungus isolated from A. satureioides have therapeutic potential as antiglioma agent.